Differences in Hematocrit and Leukocyte Levels in Preeclampsia and Severe Preeclampsia - Wiwit Indriyani Aslina; Yuni Riska Hadi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Preeclampsia is a serious pregnancy complication characterized by hypertension occurring at a gestational age of ≥ 20 weeks. In preeclampsia, hematological changes occur due to vasospasm. Vasospasm leads to endothelial damage of blood vessels, marked by an increase in hematocrit and leukocyte levels. Objectives: This study was conducted to determine whether there is a difference in hematocrit and leukocyte levels between pregnant women with preeclampsia and severe preeclampsia. Methods: A cross-sectional, comparative study strategy was employed in this investigation. The sample for this study included all 76 pregnant patients at Genteng Regional Hospital who had preeclampsia or severe preeclampsia in 2023. 38 pregnant women with preeclampsia and 38 pregnant women with severe preeclampsia made up the two groups into which the sample was split. Results: The findings of the study indicated that there is a significant difference in hematocrit levels between preeclampsia and severe preeclampsia, with the p-value = 0.001 being less than α = 0.05. Furthermore, the findings revealed a significant difference in leukocyte counts between preeclampsia and severe preeclampsia, with a p-value = 0.003, which is likewise less than α = 0.05. Conclusions: There is a significant difference in hematocrit and leukocytes in pregnant women with PE and PEB at Genteng Regional Hospital in 2024.